Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13012-022-01206-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers for deprescribing benzodiazepine receptor agonists in older adults: a systematic review of qualitative and quantitative studies using the theoretical domains framework

Abstract: Background Many strategies aimed at deprescribing benzodiazepine receptor agonists (BZRA) in older adults have already been evaluated with various success rates. There is so far no consensus on which strategy components increase deprescribing the most. Yet, despite an unfavourable benefit-to-risk ratio, BZRA use among older adults remains high. We systematically reviewed barriers and enablers for BZRA deprescribing in older adults. Methods Two revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…However, some clinicians believe that APP can speed up effect, increase adherence or further reduce psychotic symptoms, 4,33 making them more reluctant to deprescribe, especially during the acute psychotic state 33 . The barrier to deprescribing thus appears to be more related to psychiatrists than patients, which is different from what is observed for benzodiazepines, where the barriers come from both sides 34 . However, the patient or family barrier to deprescribing cannot be excluded, and as it has never been specifically addressed in schizophrenia, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some clinicians believe that APP can speed up effect, increase adherence or further reduce psychotic symptoms, 4,33 making them more reluctant to deprescribe, especially during the acute psychotic state 33 . The barrier to deprescribing thus appears to be more related to psychiatrists than patients, which is different from what is observed for benzodiazepines, where the barriers come from both sides 34 . However, the patient or family barrier to deprescribing cannot be excluded, and as it has never been specifically addressed in schizophrenia, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…33 The barrier to deprescribing thus appears to be more related to psychiatrists than patients, which is different from what is observed for benzodiazepines, where the barriers come from both sides. 34 However, the patient or family barrier to deprescribing cannot be excluded, and as it has never been specifically addressed in schizophrenia, further studies are needed. Nevertheless, this result may help convince clinicians that deprescribing is a possible option, even for the more severely affected patients.…”
Section: Other Psychotropic and Anticholinergic Prescribing Patternsmentioning
confidence: 99%
“…Two recent systematic reviews reported barriers and enablers for BZRA deprescribing among older adults, with most studies included coming from the ambulatory setting, and fewer studies from the NH setting. 14 , 15 One of these systematic reviews, also used the TDF, 15 and found common relevant TDF domains: Beliefs about capabilities, Beliefs about consequences, Environmental context and resources, Goals, Social influences , and Memory attention and decision process . Intention was also highlighted as relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important, as a previous systematic review reported the views of some healthcare providers', including pharmacists, had not been elicited. 15 Importantly, data saturation was reached for all interview groups. Finally, the trustworthiness of our results was also strengthened by investigator and data source triangulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation